The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/icesjms/fsx065
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the conceptual framework of the spatial population structure and life history of jack mackerel in the eastern South Pacific: an oceanic seamount region as potential spawning/nursery habitat

Abstract: Juvenile jack mackerel were found in 2009 in the Challenger break and the East Pacific ridge (CHAEPR). This seamount region is ∼3500 km from the coastal historic jack mackerel nursery grounds off Chile (north of 30°S). We reviewed historic evidence of juveniles around this seamount and data on several local environmental conditions: sea surface temperature, chlorophyll-a, wind, turbulence levels, and Eddy kinetic energy (EKE). A Lagrangian model for the early life stages of jack mackerel in the eastern South P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Furthermore, the spawning season has probably also a significant influence on the difference in lipid content found in mackerel and jack mackerel. In the current work, both species were captured in winter, that is, out of their spawning season which takes place in spring and summer [17,18]. However, in our previous study, they were captured in summer.…”
Section: Lipid Amount and Fatty Acid Content In Fishmentioning
confidence: 77%
“…Furthermore, the spawning season has probably also a significant influence on the difference in lipid content found in mackerel and jack mackerel. In the current work, both species were captured in winter, that is, out of their spawning season which takes place in spring and summer [17,18]. However, in our previous study, they were captured in summer.…”
Section: Lipid Amount and Fatty Acid Content In Fishmentioning
confidence: 77%
“…Front data were radioed daily to Dr. Nikolay A. Shurunov, a fisheries oceanographer aboard the Russian trawler Pioner Nikolayeva, which shadowed R/V Dmitriy Mendeleyev for a month, using the near-real time front data to increase fishing efficiency. The affinity of Trachurus murphyi to the Subtropical Front in the South Pacific has been confirmed in numerous studies and exploited by fishers (Ashford et al, 2011;Parada et al, 2017).…”
Section: Introductionmentioning
confidence: 80%
“…murphyi have a reproductive strategy to disperse over their spawning oceanic area associated to SST warmer than 15-16 °C (Cubillos et al 2008). According to Vasquez et al (2013), the reproductive activity of T. murphyi is highly correlated with the Subtropical Convergence or Subtropical Front (STF), which separates relatively warm and salty tropical waters from colder and fresher Subantarctic waters (Vasquez et al 2013, Parada et al 2017. The results indicate that SST is an important variable explaining the presence of atresia in T. murphyi, and eventually SST higher or lower than the optimal temperature for spawning, could generate a mismatch between reproduction and optimal environmental conditions for progeny development (Miranda et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, otolith chemistry indicates that all adult Chilean jack mackerel come from the same oceanic spawning area (Ashford et al 2011). Recently, Parada et al (2017) indicated the presence of a potential new spawning and nursery ground area associated with the seamount region in the Challenger break and the East Pacific ridge (32°S-39°S and 105°-126°W).…”
Section: Ethical Statementmentioning
confidence: 99%